Pediatrics Germ Cell Tumors: A Ten Year Audit in a Cancer Center of Nepal - Sharma, Krishna Sagar; Mehta, S; Misra, D; Pariyar, Jitendra; Panthi, Sabita (Nepalese Journal of Cancer, 2020)
Introduction: Pediatric Germ cell tumors are rare disease in pediatric and adolescent age group. Germ cell tumors are the most frequently found malignancies which are highly chemo sensitive. GCTs are curable if diagnosed and treated adequately even in resources poor setting in resource constraints countries like Nepal. Objective: To study the clinic pathological profile and treatment outcome of Pediatrics Germ cell tumors (GCTs) among children and adolescent group seeking treatment at B.P. Koirala Memorial Cancer Hospital (BPKMCH), Nepal. Methodology: Descriptive study was done at BPKMCH Nepal. All available case records of pediatric and adolescent girls diagnosed to have GCTs from 2002 to 2011 were collected and analyzed in terms of age, clinical features, malignancy types, treatment modalities and outcome. Results: Total 70 girls were with female gynecological malignancy. There are 46 (76.66%) with ovarian malignancies. Among the ovarian cancers, 42 had malignant germ cell cancer (91.3%) among all ovarian malignancies which are enrolled in the study. The commonest presentation was abdominal distension and pain in70%. Onset of symptoms ranged from three days to 730 days (mean 95 days). Disease stage at presentation was early stage 18 (30%) and advanced disseminated disease 42 (70%). In treatment modality, 8 (13.33%) underwent fertility sparing surgery only, 21(35%) underwent chemotherapy only and 31(51.66%) underwent multimodality treatment. 82.5% patients who were completed recommended treatment were cured. Conclusion: Malignant germ cell cancer is the commonest ovarian malignancies among pediatric and adolescent girls. Early presentation and prompt appropriate treatment would offer chances of cure even with preservation of fertility.